Há festa na família…: contributos da psicologia para o estudo de rotinas, tradições, celebrações e rituais familiares - Pinto, Helena Rebelo (2010)
This paper includes a review of the literature on routines, traditions, celebrations and rituals and adopts the family as a sociological background and a family psychological model as a conceptual reference. In particular, the Family Life Cycle (Carter & McGoldrick, 2001) and concepts are deployed as a theoretical framework to analyse types, nature and senses of festivity, within the family group. The importance of family as a situational concept proved useful in generating a better understanding of festivity. These theoretical concepts facilitate the analysis of their multiple expressions and functions in different cultural contexts, for the family as a group and for the development of participants. The opportunity for educational, social or therapeutic interventions are also pointed out.